2018
DOI: 10.18553/jmcp.2018.24.6.514
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Ribociclib plus Letrozole Versus Palbociclib plus Letrozole and Letrozole Monotherapy in the First-Line Treatment of Postmenopausal Women with HR+/HER2- Advanced or Metastatic Breast Cancer: A U.S. Payer Perspective

Abstract: Funding for this study was provided by Novartis, which manufactures ribociclib and provided input on the study design and data collection, analysis, and interpretation. Mistry, May, Suri, and Young are employees of PAREXEL. Tang, Mishra, D. Bhattacharyya, and Dalal are employees of Novartis. S. Bhattacharyya was an employee of Novartis during the study period. Tang and Dalal hold stock in Novartis. Brixner, Oderda, and Biskupiak were paid by Millcreek Outcomes Group as consultants for work on this project. Bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 30 publications
3
72
1
Order By: Relevance
“…Our findings on the drug acquisition costs are broadly consistent with three studies conducted in the USA and the UK that found that the major component of the pharmaceutical therapy costs is the CDKi treatment. 31–33 The main driver of ADR costs was found to be the haematological adverse events, an outcome that is congruent with the findings of a study assessing the cost-effectiveness of palbociclib or ribociclib in the treatment of advanced HR-positive, HER2 breast cancer in the USA. 33 …”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our findings on the drug acquisition costs are broadly consistent with three studies conducted in the USA and the UK that found that the major component of the pharmaceutical therapy costs is the CDKi treatment. 31–33 The main driver of ADR costs was found to be the haematological adverse events, an outcome that is congruent with the findings of a study assessing the cost-effectiveness of palbociclib or ribociclib in the treatment of advanced HR-positive, HER2 breast cancer in the USA. 33 …”
Section: Discussionsupporting
confidence: 71%
“…The economic burden to payers associated with the acute treatment of these adverse events was calculated based on the Diagnostic-Related Groups tariff issued by the MoH ( online supplementary table 1 ). 31 …”
Section: Methodsmentioning
confidence: 99%
“…We used a standard AUC, 6 mg/mL/min, and assumed male sex, 65 years old, body weight, 70-kg, height, 178-cm, body surface area, 1.84 m 2 , and serum creatinine, 1 ( 23 ). The price was derived from the Centers for Medicare & Medicaid Services and published articles, and the details were demonstrated in Table 1 and Supplementary Table 3 ( 24 – 26 , 31 33 ). The costs of radiographic examination covered computed tomography (CT) (every 6 weeks after treatment and every 9 weeks after progression) ( 32 ).…”
Section: Methodsmentioning
confidence: 99%
“…The costs of AEs were based on the published literature [21,[26][27][28][29]. The follow-up costs covered fees for computed tomography [30] (baseline estimate; week 12; every 6 weeks in first 45 months; every 12 weeks thereafter) and laboratory evaluations [31] (regularly throughout the treatment period and for 30 days thereafter). Costs were adjusted to present 2019 U.S. dollars, and the U.S. Consumer Price Index was adopted as a reference for inflation.…”
Section: Utility and Cost Estimatesmentioning
confidence: 99%